Efficacy of sexual stimulation in the treatment of distal ureteral stones: A meta-analysis - Cheng-Xia Peng; Ming-Hui Zhou; Dan-Ping Zhao; Guang-Hao Wu; Li Xu; Chao Feng (Heliyon, 2024)
Introduction: This study aimed to compare the clinical efficacy of sexual stimulation with that of placebo in the treatment of distal ureteral stones. Methods: We searched PubMed, Web of Science, Cochrane Library, and Google Scholar from January 1, 2000 to December 31, 2022 for studies comparing the efficacy of sexual stimulus with that of placebo for the treatment of distal ureteral stones. RevMan 5.3 software was used to pool the data. The study protocol was registered on PROSPERO (Registration Number: CRD42023432408). Results: A total of six randomized controlled trials comprising 535 cases of distal ureteral stones were included in this study. Among these, 273 cases were associated with sexual intercourse or masturbation 3–4 times a week, while 262 cases only received symptomatic treatment. The pooled results showed that the 2-week [risk ratios (RR) = 1.77, 95 % confidence interval (CI): 1.34, 2.33] and 4-week [RR = 1.48, 95 % CI: 1.29, 1.69] ureteral stone expulsion rates of the sexually stimulated group were significantly higher than those of the placebo group (ps < 0.01). Additionally, sexual stimulation was associated with a shorter ureteral stone expulsion time [weighted mean differences (WMD) = −3.74, 95 % CI: −6.27, −1.22, p < 0.01] and a decreased prevalence of renal colic attacks [WMD = −0.61, 95 % CI: −1.01, −0.22, p < 0.01] compared with those of the placebo group. Conclusion: Appropriate sexual stimulation can enhance the spontaneous expulsion of distal ureteral stones in patients presenting with tolerable pain.